DEVELOPING AND IMPLEMENTING INSTRUCTIONAL MATERIAL ENGLISH FOR SCIENCE THROUGH LESSON STUDY - Pamelasari, Stephani Diah; Wusqo, Indah Urwatin; Hardianti, Risa Dwita (Unnes Science Education Journal, 2017)
English Language Teaching in Integrated Science Department is often challenging to train students to understand science content in English and present it fluently. In the implementation of daily lecturing activities Basic English theories such as grammatical structure and IPA content are taught separately. This causes no integration between the two materials. Based on the problems an instructional material that integrates the basic theory of English and science content is needed to support the learning activities. This product is designed to improve previously unstructured instructional materials. The product developed through lesson study stages. In the Plan stage, the need analysis and product development were conducted. While at the Do stage, the instructional material was implemented in the learning process. Finally is the See stage, this stage is a reflection on the whole process of lecturing both in the process and products used. The instructional material was validated by language, content and media experts and it can be said to be feasible to use in the learning process. Then the product was used in learning process and can help students to improve the English proficiency in science with an average of 80.